2021
DOI: 10.18543/tjhe-8(2)-2021pp55-83
|View full text |Cite
|
Sign up to set email alerts
|

The Generic skills challenge for higher education institutions: Experience of public universities in Chile

Abstract: In recent decades in Chile, generic skills have been made explicit in the graduation profiles and curricula of all programs of higher education institutions, following global trends that relate to labor market expectations on the employability of graduates. The institutional characteristics, mission, educational model, and institutional seal condition the choice of the generic skills that are developed. There are no current standards for the process of definition of generic skills sets in the various programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…This may have influenced the finding of similar results (Vargas, 2011). Regardless of the country, these generic competences are evaluated based on the graduate profile in public and private universities in order to meet the trends and demands of the company and the needs of the global market (Sandoval and Ormazábal, 2021). Huaiquilaf-Jorquera et al (2021) found that graduates were unable to attribute meaning to the generic competencies described in the graduate profile because they were not clear about what each one implies.…”
Section: Discussionmentioning
confidence: 99%
“…This may have influenced the finding of similar results (Vargas, 2011). Regardless of the country, these generic competences are evaluated based on the graduate profile in public and private universities in order to meet the trends and demands of the company and the needs of the global market (Sandoval and Ormazábal, 2021). Huaiquilaf-Jorquera et al (2021) found that graduates were unable to attribute meaning to the generic competencies described in the graduate profile because they were not clear about what each one implies.…”
Section: Discussionmentioning
confidence: 99%
“…And Teachers/Faculty need to have 12 Generic Skills to do efficient teaching. They are a) Oral and Written Communication [15] b) Research and Innovation [15] c) Problem Solving [15] d) Commitment to quality [15] e) Information and Communication Technology (ICT) [15] f) Critical Evaluation [15] g) Team Work [15] h) Adaptability and Sustainability [15] i) Independent Lifelong Learning [15] j) Leadership and Decision-making [15] k) Ethical Standards [15] l) Responsibility and Accountability [15].…”
Section: Literature Surveymentioning
confidence: 99%
“…Skilling is a life-long process not limited to training institutes or the education sector. Man continuously learns new skills as age progresses and evolves into better [15] e) Information and Communication Technology (ICT) [15] f) Critical Evaluation [15] g) Team Work [15] h) Adaptability and Sustainability [15] i) Independent Lifelong Learning [15] j) Leadership and Decision-making [15] k) Ethical Standards [15] l) Responsibility and Accountability [15]. The Information and Communication Technology (ICT) according to [16] is defined as is a combination of traditional knowledge of computer and communications technology to store, process, and transmit any data (including text, audio, image, video) [16].…”
Section: Introductionmentioning
confidence: 99%